Humanities and the future notion of societal impact - Mønsted, Bolette Rye (Academic Quarter | Akademisk kvarter, 2016)
In this article, the author relates various areas such as Higher Education, social media, educational politics, society and humanistic research in regards to comment on the challenges faced by Humanities and its future notion of societal impact. It is argued that in order to identify and understand the future impact of the Humanities, it is necessary to develop a methodologically and theoretically based mapping design in which the complexity of the development can be understood and explored. The article draws upon the PhD thesis Ad nye veje (Mønsted 2015) in which a specific study programme in Higher Education in Denmark is explored as an educational example of both the development and future of Humanities and its notion of impact. The specific study programme in question is a humanities-based Higher Educational programme called Humanistic Informatics at Aalborg University. The collective purpose of the article is therefore to look upon the recent development within this specific Higher Educational programme as an important and unique type of humanistic societal impact.